Systematic Literature Review: Efektivitas Pembelajaran Berbasis E-Learning pada Perguruan Tinggi di Era Society 5.0 - Lutfi Lutfi; Risma Haris; Akhmad Kurnia; Ardiansah Hasin; Wahyu Siswanto (Journal on Education, 2024)
The use of e-learning in higher education as a technological innovation in society 5.0 era learning has a significant impact on the process of organizing education. This research is a systematic literature review published in journals between 2020-2024 to identify the number of publications per year related to the effectiveness of e-learning, the advantages of e-learning and the effectiveness of e-learning in higher education. The results of the literature review show that the effectiveness of e-learning implementation in higher education is a research topic that has been carried out in many countries with various integration models and technologies, e-learning has various advantages compared to conventional learning but must be supported by the availability of supporting systems and facilities and human resource capabilities, the effectiveness of e-learning implementation in higher education can provide different results according to the ability of universities to provide supporting systems and facilities and their management capabilities.